2020
DOI: 10.1029/2019jg005325
|View full text |Cite
|
Sign up to set email alerts
|

Winter CO2 Efflux From Sagebrush Shrublands Distributed Across the Rain‐to‐Snow Transition Zone

Abstract: The projected shifts in winter weather and snowpack conditions are expected to impact carbon storage in western U.S. rangelands. Sagebrush shrublands comprise much of the western United States, yet contribution of winter CO2 efflux to the overall carbon budget of these ecosystems remains uncertain. We explored factors controlling winter CO2 efflux measured using eddy covariance at five sagebrush‐dominated sites along an elevation/climate transect extending from 1,425 to 2,111 m. Results showed that winter CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…In spruce forests in western Sichuan, China, it was found that the average Rs rate under snow removal treatment was 0.52 µmol•m −2 •s −1 , which reduced the average winter Rs rate by 21.02% [17]. Similarly, snow removal in wetlands and tundra reduced the average Rs rate in winter [20][21][22]. But some other studies have found completely contrary results that snow removal increased the degree of soil freezing, resulting in a 27.6% increase in Rs, and the reason could be that fine root mortality increased linearly with soil freezing severity induced by colder temperature under the treatment of reduction of snow cover and it provided a substrate for heterotrophic respiration [23].…”
Section: Introductionmentioning
confidence: 99%
“…In spruce forests in western Sichuan, China, it was found that the average Rs rate under snow removal treatment was 0.52 µmol•m −2 •s −1 , which reduced the average winter Rs rate by 21.02% [17]. Similarly, snow removal in wetlands and tundra reduced the average Rs rate in winter [20][21][22]. But some other studies have found completely contrary results that snow removal increased the degree of soil freezing, resulting in a 27.6% increase in Rs, and the reason could be that fine root mortality increased linearly with soil freezing severity induced by colder temperature under the treatment of reduction of snow cover and it provided a substrate for heterotrophic respiration [23].…”
Section: Introductionmentioning
confidence: 99%